PENGARUH PEMBELAJARAN MATEMATIKA REALISTIK TERHADAP HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Muhammad Ilham S; Baharullah Baharullah; Andi Ardhila Wahyudi (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2022)
This research is motivated by the low ability of students to solve problems resulting in low learning outcomes in mathematics. Therefore, it is necessary to solve problems related to these problems by applying Realistic Mathematics Learning. The type of research used is pre-experimental research which aims to determine the effect of real mathematics learning on the learning outcomes of elementary school students. The research design used was The One Group pretest-posttest design. Data collection techniques in this study were carried out using test techniques. The data analysis technique used paired sample t-test. The results showed that the average mathematics learning outcomes score before treatment was 73.17, and after treatment was 82.96. While the results of inferential statistical analysis showed that the score of the p-value (sig (2-takes)) was 0.000 <0.05. From the results of this study, it can be concluded that Realistic Mathematics Learning has a significant effect on elementary school students' mathematics learning outcomes.